Hubungan Tingkat Pengetahuan Kebencanaan Dengan Kesiapsiagaan Bencana Pada Santri di Pondok Pesantren - Laura Nurkusuma Rahmawati; Nurul Hidayah (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Disasters are life-threatening events, whether caused by natural, non-natural, or human factors. Globally and nationally, the frequency of disasters continues to increase, with floods being the most prevalent type. Children and adolescents (aged 13–18) are a highly vulnerable population due to limited understanding of disaster mitigation. This vulnerability is particularly evident in Islamic boarding schools (pesantren) in Jombang Regency. The location of the Islamic boarding school, flanked by three major rivers (the Gedang, Gude, and Tambak Beras Rivers), places it at high risk of flooding. Furthermore, dense building density, untidy electrical installations, and the use of unsafe electronic devices increase the risk of fire. The lack of mitigation education and adequate infrastructure exacerbates the potential for loss of life in Islamic boarding schools. This study highlights the need to strengthen disaster preparedness for students as an effort to reduce disaster risk in religious-based educational institutions. Objective: This study to identify determine the relationship between the level of disaster knowledge and disaster preparedness among male and female students at Islamic boarding schools. Methods: This article used a quantitative research method with a cross-sectional design. Univariate analysis was used to analyze the data by creating a frequency distribution based on the categories of each variable. Bivariate analysis used the Spearman Rank Test. Results: The results of statistical tests using the Spearman Rank Test obtained a significance value of p = 0.0 (p < 0.05) with a correlation value of r = 0.505. This indicates that there is a fairly strong positive relationship between the level of knowledge and disaster preparedness of male and female students at Islamic Boarding Schools. Conclusion: There is a significant, positive, and fairly strong relationship between disaster knowledge levels and disaster preparedness among Islamic boarding school students.